Growth of Oyster Mushrooms Using Variations of Growing Media - Restu, Adam; Muhlis, Muhlis; Bachtiar, Imam (Jurnal Biologi Tropis, 2025)
Increasing community-based agribusiness, especially through mushroom cultivation, has become a strategic alternative in overcoming food security and economic empowerment problems. This study aims to determine the effect of various growing media on the growth of white oyster mushrooms (Pleurotus ostreatus). The experimental design used was a Randomized Group Design (RAK) with four treatments: 100% sawdust (control), 70% sawdust + 30% cardboard, 70% sawdust + 30% coconut fiber, and 70% sawdust + 30% corn cob. Data were analyzed using one-way ANOVA test and BNT at 5% significance level. The results showed that the 70% sawdust + 30% corn cob treatment produced the highest average mushroom weight (141.75 g) and the longest mycelium growth (4.05 cm), significantly outperforming the other treatments. This study concluded that corn cob waste is an effective alternative medium for oyster mushroom cultivation. This finding implies a promising application of agricultural waste in sustainable mushroom cultivation and offers a cheap and environmentally friendly solution for small-scale agribusiness. Further research is recommended to explore other waste combinations and optimize the media formulation for commercial scale production.